Imidazo[2,1-b] [1,3,4]thiadiazole: A Versatile Scaffold in Anticancer Drug Discovery - Impact of C-2, C-5, and C-6 Substitutions - Govindaiah, Shivaraja; Mokshanatha, Praveen Beekanahalli; Hudiyanti, Dwi; Majid, Fadzilah Adibah Abdul; Wan, Wan Mohd Norsani Bin (Mini Reviews in Medicinal Chemistry, 2025)
Imidazo[2,1-b][1,3,4]thiadiazoles, a class of fused bicyclic heterocycles, have garnered significant interest in medicinal chemistry due to their diverse biological activities, particularly their anticancer properties. Over recent decades, extensive research has been conducted to explore and enhance their therapeutic potential. This comprehensive review spans six decades of research on the imidazo[2,1-b][1,3,4]thiadiazole scaffold, focusing on structural variations at C-2, C-5, and C-6 position on this scaffold and their implications for anticancer activity. Modifications at these positions have been shown to significantly impact the compound’s efficacy against various cancer cell lines. Continuous exploration and optimization of these substitutions hold promise for the development of novel anticancer therapeutics.
Keywords: scaffold